Transoral Ultrasound in the Diagnosis of Obstructive Salivary Gland Pathologies - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Ultrasound in Medicine and Biology, 2019)
Transcutaneous ultrasound (TCUS) is an accepted diagnostic method in salivary gland diseases. However, sparse data are available on the use of transoral ultrasound (TOUS) in sialadenopathies. One hundred five patients presenting with various obstructive sialadenopathies were examined using TOUS and TCUS. Ultrasound findings were validated by direct visualization in subsequent sialendoscopy examinations. By TOUS, but not by TCUS, all patients with sialolithiasis (70/105) could be identified and virtually all concrements, even very small ones, were detected and distinguished from artifacts. Ductal stenoses (16/105) could be correctly differentiated from sialoliths, and exceptional insights into the delicate anatomy of parotid duct stenoses were gained. TOUS provided detailed information on other space-occupying lesions (14/105) and circumvented the method-related diagnostic weaknesses of TCUS. As a valuable tool in the diagnosis of obstructive sialadenopathies, TOUS seems superior to TCUS in pathologies involving the distal parotid duct, the submandibular duct system and the floor of the mouth.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Obstructive sialadenopathy; Salivary duct stenosis; Salivary glands; Sialolithiasis; Transoral ultrasound